Pelatihan Konseling Kelompok dengan Menggunakan Teknik M3 (Mendengar, Memahami, Merangkul) sebagai Upaya Peduli Kesehatan Mental Generasi Alpha di MAN 1 Bekasi: Group Counseling Training Using the Listening, Understanding, Embracing Technique as an Effort to Care for the Mental Health of the Alpha Generation at MAN 1 Bekasi - Putri, Noor Lusty; Andiri, Sisca Pri; Trisetiyaningsih, Yanita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Depression, anxiety, and behavioral disorders are among the leading causes of illness and disability among adolescents. Suicide is the fourth leading cause of death among those aged 15-29 years. Thus, handling mental health conditions in adolescents is very important because it can impact their well-being not only during adolescence but also in their adult lives. Adolescents who experience mental health problems tend to have difficulties in various aspects of life, including learning, interacting socially, and coping with emotional stress. Good mental health in adolescents is also closely related to their ability to build healthy relationships in adulthood. One method that has been proven effective in improving the psychological well-being of adolescents is through group counseling. This activity was carried out in November 2024, targeting adolescents at MAN 1 Bekasi. The number of participants in this activity was 30 students. This activity began with a pretest, education, group counseling, and a post-test. The pretest results obtained a minimum score of 1, a maximum score of 25, and an average score of 17.4. Based on the results of the participant evaluation through the posttest, the results obtained a minimum score of 7, a maximum score of 30, and an average score of 21.7. There was an increase in the knowledge score of 4.3. From the results of the group counseling evaluation, each participant was able to carry out group dynamics well in adolescent mental health counseling. It is hoped that this activity will continue routinely to screen adolescent mental health.